Evaluation of the sexual function of men in Kazakhstan during 2021–2022: A cross‐sectional study - Marat Sikhymbaev; Dinara Ospanova; Andrey Grzhibovsky; Merkhat Akkaliyev; Turar Kurmanbekov; Shynar Tanabayeva; Timur Saliev; Sagat Altynbekov; Ildar Fakhradiyev (Health Science Reports, 2023)
Abstract Background and Aims Assessing male sexual function is an important public health issue in every country. In Kazakhstan, there are currently no reliable statistics on male sexual function. The study aimed at the assessment of sexual function in men in Kazakhstan. Methods Men between the ages of 18 and 69 from Astana, Almaty, and Shymkent, three of Kazakhstan's biggest cities, were included in the cross‐sectional study in 2021–2022. A standardized and modified Brief Sexual Function Inventory (BSFI) tool was used for participants' interviews. The World Health Organization STEPS questionnaire was employed to gather sociodemographic information, including smoking and alcohol use. Results Respondents from three cities: n = 283 from Almaty, n = 254 from Astana, and n = 232 from Shymkent were interviewed. All participants' average age was 39.2 ± 13.4. Kazakhs made up 79.5% of the respondents by nationality; 19.1% who answered questions on physical activity verified that they were involved in high‐intensity labor. According to the BSFI questionnaire, the respondents from Shymkent had an average total score of 2.82 ± 0.92, (p ≤ 0.05), which was higher than the total scores of respondents from Almaty (2.69 ± 0.87) and Astana (2.69 ± 0.95). A relationship was found between sexual dysfunction and age indicators over 55 years. Participants with overweight had a relationship with sexual dysfunction with an odds ratio (OR): 1.84 (p = 0.01). According to the smoking factor, in study participants with sexual dysfunction, a relationship was also determined, OR: 1.42; 95% confidence interval (CI): 0.79–1.97 (p = 0.001). The presence of high‐intensity activity (OR: 1.58; 95% CI: 0.04–1.91), and physical inactivity (OR: 1.49; 95% CI: 0.89–1.97) were associated with the presence of sexual dysfunction, p ≤ 0.05. Conclusions Our research indicates that men over 50 who smoke, are overweight, and are physically inactive are at risk for sexual dysfunction. Early health promotion may be the most effective method to reduce the negative effects of sexual dysfunction on the health and wellbeing of men over 50.